Analisis Model Idiosinkratik Presiden Rodrigo Roa Duterte Atas Kebijakan War on Drugs di Filipina - Santi, Mia Krisna; Kumala Dewi, Putu Ratih; Parameswari, A.A.A Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 3 No 1 (2023): JURNAL DIKSHI, 2023)
This research aims to explain the reasons for President Rodrigo Roa Duterte in assigning a war on drugs policy which is examined through idiosyncratic aspects. This research utilized an explanatory qualitative method, with an idiosyncratic theoretical framework, a psychobiographical approach, and an idiosyncratic analysis model in policy making. This research discovers Duterte’s ambitions to protect forthcoming generations is rooted in his keen understanding of the recent situation in society regarding drug crime, which is supported by his prosperous experience as Mayor of Davao. Duterte's determination, which is represented by his vow to eradicate drugs, obliged his emphasis on the task of being eligible to solve drug problems in a relatively fast period of 3-6 months in a fairly practical way, namely killing (shooting dead) drug criminals. Duterte becomes a leader who adopts leadership styles and types of leaders who are Task Oriented and Pragmatic Directive.